Multi‐Light‐Responsive Upconversion‐and‐Downshifting‐Based Circularly Polarized Luminescent Switches in Chiral Metal–Organic Frameworks. Issue 33 (10th July 2021) - Zhao, Tonghan; Han, Jianlei; Shi, Yonghong; Zhou, Jin; Duan, Pengfei
Abstract: Metal–organic frameworks (MOFs) have attracted tremendous attention for several novel applications. However, functional MOFs with light‐responsive circularly polarized luminescence (CPL) are not examined in detail. Therefore, a dual CPL switch exhibiting both upconversion (UC) and downshifting (DS) CPL in the solid state is constructed by loading a luminescent diarylethene derivative (DAEC) and UC nanoparticles (UCNPs) into chiral MOFs. The chiral MOF⊃DAEC composites exhibit both photoswitchable luminescence and DS‐CPL properties under alternating UV and visible light irradiation. Additionally, a reversible UC‐CPL switch is realized using near‐infrared (NIR) and visible light irradiation by introducing energy‐level‐matched UCNPs and DAEC into the chiral MOFs. The dissymmetry factor ( g lum ) of UC‐CPL is noted to be significantly amplified through energy transfer compared to that of DS‐CPL, which indicates that the information on circular polarization can be manipulated by altering the incident light. A chiroptical logic circuit with a 2D information output is designed with UV, visible, and NIR light as inputs by setting a rational threshold. Abstract : Light‐regulated upconversion (UC)‐ and downshifting (DS)‐circularly polarized luminescence (CPL) switches are achieved by integrating chiral metal–organic frameworks with luminescent diarylethenes and UC nanoparticles. UC‐CPL exhibits a higher dissymmetry factor than that of DS‐CPL, and a chiroptical logic circuit with 2D information output is fabricated based on this switch.